Projection of Clean Water Needs for Bandarmasih City Water Utility (PDAM) in Banjarmasin City, in the Banjarmasin Tengah Sub-district, for the Year 2031 - Adriani Muhlis; Abdul Khaliq; Faryanto Effendie; Fakhrurrazi; Fitriani Hayati; Abdul Hafizh Ihsani (Jurnal Multidisiplin Madani, 2023)
The geographical situation of Banjarmasin City, which partly supports the availability of clean water for the community, is crucial considering the primary needs of the people by utilizing natural resources that are expected to fulfil the community's demand for clean water. The need for clean water must be met for the entire population of Banjarmasin, including the Banjarmasin Tengah Sub-district, a district in Banjarmasin, South Kalimantan Province, with an area of 6.66 km2 and a population of 91,780 people. The research method for preparing this report includes field surveys, collecting primary and secondary data, and conducting population projection calculations. A literature review was conducted by gathering, reading, and studying relevant sources such as journals and books necessary to conduct this research. Based on the analysis and discussion results, it can be concluded that the projected loss of clean water in the year 2031, assuming a standard rate of 36 L/s, is significant. The projected demand for clean water in the service area of the Central Banjarmasin branch of the PDAM in the projection year 2031 is approximately 215 L/s